2004
DOI: 10.1002/cncr.11911
|View full text |Cite
|
Sign up to set email alerts
|

Elevated perioperative serum vascular endothelial growth factor levels in patients with colon carcinoma

Abstract: BACKGROUND To the authors' knowledge, little is known to date regarding the prognostic relevance of measuring serum levels of vascular endothelial growth factor (VEGF), a potent stimulator of angiogenesis, in patients with colon carcinoma who undergo surgery. METHODS Preoperative and postoperative VEGF serum levels were determined by enzyme‐linked immunoadsorbent assay in 81 patients with colon carcinoma who were undergoing surgery. Fifty healthy individuals served to define normal VEGF serum levels. RESULTS P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 17 publications
6
63
0
5
Order By: Relevance
“…It promotes the proliferation of vascular endothelial cells and angiogenesis (Lv et al, 2010). Serum VEGF-A is highly elevated in several types of cancer including colon (De Vita et al, 2004), cervix (Zusterzeel et al, 2009), breast and gynaecological cancer (Koukourakis et al, 2011), non-small cell lung cancer (Liang et al, 2013) and prostate (Singh et al, 2013). In our study, serum VEGF-A level was found to be significantly higher (p=0.001) in SCCHN patients as compared to healthy controls.…”
Section: Discussionsupporting
confidence: 50%
“…It promotes the proliferation of vascular endothelial cells and angiogenesis (Lv et al, 2010). Serum VEGF-A is highly elevated in several types of cancer including colon (De Vita et al, 2004), cervix (Zusterzeel et al, 2009), breast and gynaecological cancer (Koukourakis et al, 2011), non-small cell lung cancer (Liang et al, 2013) and prostate (Singh et al, 2013). In our study, serum VEGF-A level was found to be significantly higher (p=0.001) in SCCHN patients as compared to healthy controls.…”
Section: Discussionsupporting
confidence: 50%
“…This significant decline in plasma VEGF levels would make IM862 an antiangiogenic agent worth of consideration for further investigation. Effectively, some preliminary studies have linked VEGF levels with tumour burden in colon carcinoma (Nakayama et al, 2002;De Vita et al, 2004). Interestingly, VEGF levels dropped significantly after surgery and persistent elevated VEGF levels correlated with relapse, indicating significant residual disease.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF could contribute to the accumulation of immunosuppressive cells [MDSCs, regulatory T (Treg) cells, tumor-associated macrophages, and Tie-2-expressing monocytes] in tumor-bearing hosts through direct or indirect mechanisms 18) . Previous studies have shown that the serum VEGF concentration is elevated in several cancers, including gastric and colorectal cancers 19,20), and increased VEGF predicts a poor prognosis in gastric and colorectal cancers 20,21) . Cachexia due to cancer is a malnutritional status and complex metabolic disorder that includes loss of adipose tissue due to lipolysis, loss of skeletal muscle, elevation of resting energy consumption, anorexia, and reduction of food intake [22][23][24] .…”
Section: Il-17 and Vegf Are Significantly Associated With Disease Promentioning
confidence: 99%